Comparative transcriptome analysis of wheat embryo and endosperm responses to ABA and H2O2 stresses during seed germination. (December 2016) - Yu, Yonglong; Zhen, Shoumin; Wang, Shu; Wang, Yaping; Cao, Hui; Zhang, Yanzhen; Li, Jiarui; Yan, Yueming
Abstract Background Wheat embryo and endosperm play important roles in seed germination, seedling survival, and subsequent vegetative growth. ABA can positively regulate dormancy induction and negatively regulates seed germination at low concentrations, while low H2 O2 concentrations promote seed germination of cereal plants. In this report, we performed the first integrative transcriptome analysis of wheat embryo and endosperm responses to ABA and H2 O2 stresses. Results We used the GeneChip® Wheat Genome Array to conduct a comparative transcriptome microarray analysis of the embryo and endosperm of elite Chinese bread wheat cultivar Zhengmai 9023 in response to ABA and H2 O2 treatments during seed germination. Transcriptome profiling showed that after H2 O2 and ABA treatments, the 64 differentially expressed genes in the embryo were closely related to DNA synthesis, CHO metabolism, hormone metabolism, and protein degradation, while 121 in the endosperm were involved mainly in storage reserves, transport, biotic and abiotic stresses, hormone metabolism, cell wall metabolism, signaling, and development. Scatter plot analysis showed that ABA treatment increased the similarity of regulated patterns between the two tissues, whereas H2 O2 treatment decreased the global expression similarity. MapMan analysis provided a global view of changes in several important metabolism pathways (e.g., energy reserves mobilization, cell wall metabolism, and photosynthesis), as well as related functional groups (e.g., cellular processes, hormones, and signaling and transport) in the embryo and endosperm following exposure of seeds to ABA and H2 O2 treatments during germination. Quantitative RT-PCR analysis was used to validate the expression patterns of nine differentially expressed genes. Conclusions Wheat seed germination involves regulation of a large number of genes involved in many functional groups. ABA/H2 O2 can repress/promote seed germination by coordinately regulating related gene expression. Our results provide novel insights into the transcriptional regulation mechanisms of embryo and endosperm in response to ABA and H2 O2 treatments during seed germination.